2016
DOI: 10.1002/jmri.25179
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted multiparametric MRI for monitoring longitudinal changes of parameters in rabbit VX2 liver tumors

Abstract: ADC, f, and KDKI were identified as the most promising parameters for monitoring changes in rabbit liver VX2 carcinoma and f and ADC showed highest correlation with MVD. J. Magn. Reson. Imaging 2016;44:707-714.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Contrary to the treated group, moderate correlation was found between f and MVD in the control group. This correlation has been reported in pancreatic tumors in patients, in colorectal tumors in nude mice, and in VX2 liver tumors in rabbits . Hence, we believe f could serve as a noninvasive marker of tumor vascularity in its natural course of development without drug intervention.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Contrary to the treated group, moderate correlation was found between f and MVD in the control group. This correlation has been reported in pancreatic tumors in patients, in colorectal tumors in nude mice, and in VX2 liver tumors in rabbits . Hence, we believe f could serve as a noninvasive marker of tumor vascularity in its natural course of development without drug intervention.…”
Section: Discussionsupporting
confidence: 80%
“…This correlation has been reported in pancreatic tumors in patients, 34 in colorectal tumors in nude mice, 35 and in VX2 liver tumors in rabbits. 36 Hence, we believe f could serve as a noninvasive marker of tumor vascularity in its natural course of development without drug intervention. However, no correlation was found between ADC total , D, and NF in the control group as opposed to the treated group.…”
Section: Discussionmentioning
confidence: 99%
“…ADC value is always greater than D value because of including tissue diffusion and perfusion (25); it is consistent with our results. In addition, the report (26) has shown that when the b value is chosen appropriately, the ADC value can describe the tumor perfusion information. In this study, no significant correlation was found between ADC value and MVD or VEGF expression; this result was the same as Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…The f value is a substitute marker of blood volume and can be applied in monitoring the changes in blood vessels because of the reduction with the decrease of blood vessels (26). In our study, no significant correlation was found between f value and MVD or VEGF expression; the conclusion was the same as Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, the K trans and ADC continued to change 2 weeks after implantation in the current study. A previous study reported that certain diffusion MRI parameters (including ADC) may continue to change within the first month of tumor implantation ( 28 ). Therefore, the K trans and ADC changes reflect the tumor angiogenesis and tumor celluarity, which may be the result of tumor physiological indicators and thus, may occur later than the changes in physiological indicators.…”
Section: Discussionmentioning
confidence: 99%